Pengaruh Indeks Bursa Saham Regional Asia Pasifik terhadap Indeks Harga Saham Gabungan (IHSG) pada Bursa Efek Indonesia (BEI) Periode Tahun 2009-2011 - Pramudika, Gading; pandi, Kus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study was developed with the aim to analyze and determine the development of the stock market index asia pacific region in relation to the Indonesia Stock Exchange (IDX) and to investigate the influence of stock market index asia pacific simultaneously or partially represented by four of the ten regional stock market index asia pacific against BEI index. The tenth regional stock market index asia pacific is representing the ASX and NZX Pacific regional stock exchanges as well as SSE, Hang Seng, BSE Sensex, FTSE, Nikkei, SGX and TSE are depreciated KOSPI into four, namely SSE, Nikkei, NZX and the KOSPI as other indices did not meet the study criteria. Judgment sampling method used to collect data for 153 weeks from 2009 to 2011. The study was conducted using multiple linear regression analysis as an analytical model. The analysis model to analyze the influence of the ten regional stock market index asia pacific, either simultaneously or individually to the BEI index. The results showed that the effect of global stock indices jointly significant influence but individually only SSE and Nikkei indices that affect BEI index. Keywords: Stock market index asia pacific region, BEI index and multiple linear regression analysis